Defoliation of sweet corn plants under irrigation depths and its impact on gas exchange - Osvaldir F. dos Santos; Sebastião F. de Lima; Vespasiano B. de Paiva Neto; Gabriel L. Piati; Christian R. W. de S. Osório; Hugo M. de Souza (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The objective of this work was to evaluate leaf gas exchanges of sweet corn as a function of defoliation when submitted to different irrigation depths. The experimental design was randomized blocks in split-plot scheme, with four irrigation depths in the plots [50, 75, 100 and 125% of crop evapotranspiration (ETc)], and three levels of defoliation in the subplots (0%, control; 35%, removal of four fully expanded leaves; 100%, total removal of the leaves - section of the aerial part) with three replicates. Defoliation was manually performed when the plant had four fully expanded leaves. It was verified that the dephs of irrigation and defoliation levels affect leaf gas exchanges in sweet corn plants, allowing the conclusion that the plant tends to activate a mechanism of photosynthetic compensation, when subjected to leaf stress, which can vary according to the degree of severity and water availability to which it is submitted. The most expressive values of gas exchanges in sweet corn plants that did not have defoliation were generally observed at irrigation depths estimated between 87 and 99% ETc and, in the treatments with defoliation, regardless of the level, at irrigation depth of 125% ETc.